Fabrication and characterization of surgical sutures with propolis silver nano particles and analysis of its antimicrobial properties - Selvaraju, Gayathri Devi; Umapathy, Vidhya Rekha; Sumathijones, C.; Singh Cheema, Manraj; Jayamani, D. Rachael; Dharani, R. (Elsevier, 2022)
Objectives: The objective of this work was to synthesize propolis – silver nanoparticles, coat the prepared nanoparticles on surgical sutures, characterize the coated sutures and to study the antimicrobial activity of coated sutures against human pathogenic microorganisms. Methods: Silver nanoparticles were synthesized with ethanolic propolis extract and analyzed by UV spectrophotometry analysis. Absorption peak was detected at 430 nm to confirm silver nanoparticle synthesis. Propolis – silver nanoparticles were coated over plain Cal Gut surgical sutures with the help of sodium alginate by slurry dipping technique. The characterization of coated sutures was done by Fourier-Transform Infrared analysis (FTIR) analysis and Scanning Electron Microscopy (SEM). The antimicrobial activity of propolis silver nanoparticles was determined by disc diffusion method against pathogenic bacteria like Staphylococcus aureus, E.coli and Aspergillus flavus obtained from clinical samples. Results: FTIR confirmed the presence of silver through its various peaks and the various functional groups were detected. The SEM characterization revealed the particles size and shape of the nanoparticle at a magnification of 20KV. The size is about 20 nm and its mostly spherical in shape. The surface of the coated sutures was rough indicating the coating of propolis – silver nanoparticles (AgNPs) over the sutures. The in-vitro antimicrobial assay showed that the propolis – silver nanoparticles and the also coated sutures possessed a significant anti-microbial activity against the clinical pathogenic microorganisms. Conclusion: Propolis is a natural product which is an asset to the mankind. The combined effect of the propolis and silver nanoparticles and also the antimicrobial activity of propolis nanoparticle coated sutures were extensively studied. So, this synergistic drug can be used as antimicrobial materials for clinical practice and bio medical use. It is proved that propolis silver nanoparticle loaded sutures are a beneficial in preventing the surgical site infections.